2021
DOI: 10.7717/peerj.12245
|View full text |Cite
|
Sign up to set email alerts
|

Reducing publication delay to improve the efficiency and impact of conservation science

Abstract: Evidence-based decision-making is most effective with comprehensive access to scientific studies. If studies face significant publication delays or barriers, the useful information they contain may not reach decision-makers in a timely manner. This represents a potential problem for mission-oriented disciplines where access to the latest data is required to ensure effective actions are undertaken. We sought to analyse the severity of publication delay in conservation science—a field that requires urgent action… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…This hinders research, as long‐term studies contribute disproportionately both to scientific understanding and to policy in ecology (Hughes et al, 2017; Mills et al, 2015). Long publication delays are also problematic, as they reduce researcher, practitioner and funder access to the latest and most relevant research, which creates an inefficient research environment (Christie et al, 2021). Here, we show that publication delay is 4.0 ± 0.1 years (mean ± standard error), which is longer than delays in the related field of conservation science (3.2 ± 0.1) (Christie et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hinders research, as long‐term studies contribute disproportionately both to scientific understanding and to policy in ecology (Hughes et al, 2017; Mills et al, 2015). Long publication delays are also problematic, as they reduce researcher, practitioner and funder access to the latest and most relevant research, which creates an inefficient research environment (Christie et al, 2021). Here, we show that publication delay is 4.0 ± 0.1 years (mean ± standard error), which is longer than delays in the related field of conservation science (3.2 ± 0.1) (Christie et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Long publication delays are also problematic, as they reduce researcher, practitioner and funder access to the latest and most relevant research, which creates an inefficient research environment (Christie et al, 2021). Here, we show that publication delay is 4.0 ± 0.1 years (mean ± standard error), which is longer than delays in the related field of conservation science (3.2 ± 0.1) (Christie et al, 2021). Visual inspection of publication delay through time using LOESS smoothers showed that this has been relatively constant, with some reduction in the last 15 years (approximately −0.7‐year delay; Figure 9b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication delay, the time gap between finishing data collection and publication, has increased over time from ~ 1.4 ± 0.2 years in 1912 to 2.6 ± 0.1 years in 2020 and 3.2 ± 0.1 in 2021 ( 66 ). Furthermore, biased peer review processes ( 38 , 67 ) and unethical publishing practices such as plagiarism, data fabrication, manipulation, and data beautification ( 68 , 69 ) are unsolved problems in scientific publishing.…”
Section: The Challenges Of Scientific Publishingmentioning
confidence: 99%
“…Publication times determine the dissemination of important findings, which further affects their contribution to scientific progress. Timely publication may promote positive communication at academic conferences ( Vosshall, 2012 ), provide the latest evidence for secondary research ( Yu, Rong & Li, 2003 ), and enable patients to benefit from treatments based on the best evidence ( Shephard, 1973 ) and decision makers to make reasonable and beneficial decisions ( Christie et al, 2021 ). In addition to promoting scientific developments, the publication of research also bears witness to researchers’ contributions.…”
Section: Introductionmentioning
confidence: 99%